Digital altruism: strategi kepercayaan pendonasi Kitabisa.com dalam membangun solidaritas sosial (Jurnal Kajian Media, 2020)
- The digital world continues to develop today in all fields of life. The presence of the internet and its digitalization further enliven business, social activities, education, and others. One of the humanitarian activities in building social solidarity that is currently developing and supported by digitalization is fundraising or crowdfunding activities. Fundraising is an activity that is not easy to do. In collecting funds it is not uncommon to have distrust from people or institutions that want to make donations. Especially nowadays where a lot of fraud occurs, including in fundraising. The credibility of donation search institutions is also one of the considerations of donors. One of the institutions that are active in digital-based fundraising is Kitabisa.com. In the course of the book, Kitabisa.com was a success and was successful in every digital campaign. Departing from this, in this study researchers were interested to find out how the Kitabisa.com strategy in building the trust of donors to be willing to donate money to this institution. This study uses a qualitative method, where the object of the research are the new donors and also old donors who are active donate in Kitabisa.com. The theory used as a reference in this study is the 6 elements of the Trust pyramid according to Petrovic, Ksela, Fallenbock & Kittl (2003). The six elements are (1). State of the art security, (2) Merchant Legitimacy, (3) Fulfillment, (4) Tone and Ambience, (5) Customer Control and (6) Consumer Collaboration. The Research shows that the six components are taken into account by the institution Kitabisa.com in building trust for their donors. In addition, in terms of donation, this is their reference in making donations to trusted institutions to support solidarism.  Keywords: Digital Altruism; Strategy; Trust; Donation; Social Solidarity.